A Note on the Cramer-Damgard Identification Scheme - Zhao, Yunlei; Cheung, Shirley H. C.; Zang, Binyu; Zhu, Bin Benjamin (Workshop on Internet and Network Economics, 2005)
In light of the recent work of Micali and Reyzin on showing the subtleties and complexities of the soundness notions of zero-knowledge (ZK) protocols when the verifier has his public-key, we re-investigate the Cramer-Damgård intended-verifier identification scheme and show two man-in-the-middle attacks in some reasonable settings: one simple replaying attack and one ingenious interleaving attack. Our attacks are independent of the underlying hardness assumptions assumed.